Наддніпрянська традиція у сакральній архітектурі Донщини XVIII століття - Челомбітько, Ольга; Сентимрей, Юрій; Chelombitko, Olha; Sentymrei, Yrii (Видавництво Львівської політехніки, 2020)
На прикладі ряду споруд простежено вплив української наддніпрянської традиції сакральної архітектури на церковне будівництво Донщини XVIII століття. Окреслено спільні та відмінні риси подонських споруд із їх наддніпрянськими прообразами. Проаналізовано різні можливості окреслення такого роду об’єктів у рамках архітектурної теорії.

On the basis of historical graphic materials analysis, a number of Don region sacral objects were identified as those whose style and character are undoubtedly connected with the traditions of Dnieper Ukraine architecture. The influence of the Dnieper region architecture in this region is mainly associated with the main military cathedral in Cherkassk (now Starocherkassk), but, the presented materials shows a much wider scale of this phenomenon within the framework of wooden construction. Has been ascertained, that Dnieper architectural tradition is present in the whole territory of the Don region, and not only in those close to Zaporizhia and Slobozhanshchyna (Sloboda Ukraine). It is characterized by the combination of planning “octagons” (“vosmeryk”) on the principles of axial and centric symmetry, pyramid composition, accentuation of the central volume by the highest dome and more. Characteristic differences include some deviations from symmetry and the presence of a ground elevation. It is noted that among the whole complex of objects related to the Ukrainian cultural influence in the present territories of the Russian Federation (Kuban, Starodub region, East Sloboda Ukraine, Siberia, etc.), the Don region is the least researched for the identification and analysis of architectural objects in the solutions of which are traced to the Dnieper Ukraine signs. This is due primarily to the fact that, with the exception of a few stone ones, such objects ceased to exist during the nineteenth century, being replaced by new structures that has a completely different style. Since such buildings ceased to exist by the end of the nineteenth century, it has been determined that the prospective areas of further research are the study of graphic materials and documents, photographs, memories and more. Also important is the discovery of data pertaining to construction in the Don region before the eighteenth century, when its ties with the Dnieper and especially Zaporizhzhia were no less close.
The dneper Ukraine tradition in the sacred architecture of Don region in the 18th century
Keywords: традиція; Донщина; сакральна архітектура; Наддніпрянщина; Tradition; Don region (Donshchyna); sacral architecture; Dnieper Ukraine; 726